Haemophilic Arthropathy Presenting as JIA: A Case Report - Begum, Suraiya; Islam, Md Mofizul; Hafiz-Al-Mamun, Md; Rahman, Shahana A (Bangladesh Journal of Child Health, 2013)
DOI: http://dx.doi.org/10.3329/bjch.v36i3.14290 BANGLADESH J CHILD HEALTH 2012; VOL 36 (3) : 156-158